Necropolitics : Mass Graves and Exhumations in the Age of Human Rights - Ferrándiz, Francisco; Robben, Antonius C. G. M. (Book collections on Project MUSE., 2015)
The unmarked mass graves left by war and acts of terror are lasting traces of violence in communities traumatized by fear, conflict, and unfinished mourning. Like silent testimonies to the wounds of history, these graves continue to inflict harm on communities and families that wish to bury or memorialize their lost kin. Changing political circumstances can reveal the location of mass graves or facilitate their exhumation, but the challenge of identifying and recovering the dead is only the beginning of a complex process that brings the rights and wishes of a bereaved society onto a transnational stage.Necropolitics: Mass Graves and Exhumations in the Age of Human Rights examines the political and social implications of this sensitive undertaking in specific local and national contexts. International forensic methods, local-level claims, national political developments, and transnational human rights discourse converge in detailed case studies from the United States, Argentina, Chile, Peru, Spain, Bosnia-Herzegovina, Greece, Rwanda, Cambodia, and Korea. Contributors analyze the role of exhumations in transitional justice from the steps of interviewing eyewitnesses and survivors to the painstaking forensic recovery and comparison of DNA profiles. This innovative volume demonstrates that contemporary exhumations are as much a source of personal, historical, and criminal evidence as instruments of redress for victims through legal accountability and memory politics.Contributors: Zoë Crossland, Francisco Ferrándiz, Luis Fondebrider, Iosif Kovras, Heonik Kwon, Isaias Rojas-Perez, Antonius C. G. M. Robben, Elena Lesley, Katerina Stefatos, Francesc Torres, Sarah Wagner, Richard Ashby Wilson.